The Effect of Job Satisfaction on Teachers’ Creativity in Using Subsidiary Materials in Learning English in Iranian English Institutes - Fatemeh Norouzpour; Majid Pourmohammadi (Modern Perspectives in Language, Literature and Education Vol. 4, 2021)
Teachers’ job satisfaction and creativity in the teaching process are very important to the continuous growth of educational systems around the world. Satisfaction and creation at work are very essential in teachers’ lives because they form the fundamental reasons to vitalize the teaching and learning atmosphere. This study investigated the effect of job satisfaction on teachers’ creativity in using subsidiary materials among EFL teachers in English institutes. To this end, 50 teachers who were teaching EFL at “Adib”, “Alborz” and “Rouyesh No” English Institutes in Rasht, Iran were selected. They were selected based on their job experiences and their availabilities. Their English teaching experiences varied from 5 to 20 years. Their ages ranged from 20 to 50 years. They were invited to fill out a researcher-developed questionnaire. It was a questionnaire, which included 20 items and there were two parts. The first part of the questionnaire asked about job satisfaction among the teachers, and the second part asked about their creative use of subsidiary materials in classroom. The findings suggested that the teachers hold different views regarding job satisfaction and teachers with high level of job satisfaction are more creative in using subsidiary materials. Besides, job satisfaction increases creativity in using material in EFL classrooms. Furthermore, if the teachers are satisfied with their job, they develop and maintain a high level of performance and learning process would be more efficient and effective.